Crystal structures and optical properties of new quaternary strontium europium aluminate luminescent nanoribbons. Issue 4 (26th November 2014) - Li, Xufan; Budai, John D.; Liu, Feng; Chen, Yu-Sheng; Howe, Jane Y.; Sun, Chengjun; Tischler, Jonathan Z.; Meltzer, Richard S.; Pan, Zhengwei
Abstract : We report the synthesis, crystal structure characterization and optical properties of three series of new quaternary strontium europium aluminate luminescent nanoribbons with luminescence colors of blue, green and yellow. Abstract : We report the synthesis and characterization of three series of new quaternary strontium europium aluminate (Sr–Eu–Al–O; SEAO) luminescent nanoribbons that show blue, green, and yellow luminescence from localized Eu 2+ luminescent centers. These three series of SEAO nanoribbons are: blue luminescent, tetragonal Sr1− x Eu x Al6 O10 (0 < x < 1) (b-SEAO), green luminescent, monoclinic Sr1− x Eu x Al2 O4 (0 < x < 1) (g-SEAO), and yellow luminescent, hexagonal Sr1− x Eu x Al2 O4 (0 < x < 1) (y-SEAO). Among these three series of SEAO nanoribbons, the b-SEAOs and y-SEAOs are new compounds that have not been reported before. The crystal structures of the SEAO nanoribbons were comprehensively studied using various synchrotron X-ray diffraction techniques and the effects of crystal structures on materials' luminescence properties were investigated. These one-dimensional SEAO luminescent nanoribbons can function as both light generators and waveguides, and thus have promising potential as the building blocks in miniaturized photonic circuitry.